Asymmetric Synthesis of Tertiary Alcohols and Thiols via Nonstabilized Tertiary α‐Oxy‐ and α‐Thio‐Substituted Organolithium Species. Issue 36 (7th August 2017) - Pulis, Alexander P.; Varela, Ana; Citti, Cinzia; Songara, Pradip; Leonori, Daniele; Aggarwal, Varinder K.
Abstract: Nonstabilized α‐O‐substituted tertiary organolithium species are difficult to generate, and the α‐S‐substituted analogues are configurationally unstable. We now report that they can both be generated easily and trapped with a range of electrophiles with high enantioselectivity, providing ready access to a range of enantioenriched tertiary alcohols and thiols. The configurational stability of the α‐S‐organolithium species was enhanced by using a less coordinating solvent and short reaction times. Abstract : Enantioenriched, nonstabilized, tertiary organolithium species with α‐O and α‐S substitution are of remarkable configurational stability (R,  R′=alkyl). They can thus be trapped with a broad range of electrophiles to generate tertiary alcohol and tertiary thiol derivatives with excellent enantioselectivity.